49 Introduction of a physical activity assessment and exercise prescription to the cardiac risk in the young clinic. (6th October 2022) - Kearney, R; Sullivan, V; Ward, D; Connaughton, H
Abstract : Introduction: Physical activity (PA) is associated with reduced cardiovascular (CV) mortality and forms a vital part of CV disease management. The World Health Organisation (WHO) estimates that physical inactivity is responsible for approximately 30% of CV disease. The WHO 2020 Guidelines for PA in adults advocate for at least 150–300 min/week of moderate or at least 75–150 min/week of vigorous intensity aerobic activity, in addition to two or more days a week of resistance exercise. Unfortunately, only 33% of the Irish adult population achieve such PA levels. Despite PA as an evidenced based first-line management in CV disease, PA intervention is still far from standard practice. The aim of this quality improvement project was to incorporate PA assessment and Exercise Prescription (Ex Rx) as part of standard optimal care at the CRY Clinic. Methods: Patients attending the CRY Clinic between Jan-Sept 2021 self reported PA levels using the Nordic Physical Activity Questionnaire (NPAQ-short). An Ex Rx template ( table 1 ) with an exercise intensity guide ( table 2 ) alongside patient and clinical exercise resources were developed. Exercise recommendations from the recent European Society of Cardiology i and the American Heart Association/American College of Cardiology formed the resource evidence base. Exercise assessment and prescription education was provided to the CRY Clinical Staff. Data was collected using a secure Microsoft excel file over the initial 9 month period which included anonymised self reported PA levels and completed Ex Rx. Results: 763 patient PA and 33 Ex Rx data sets were collected during the 9 month period. Results of self-reported PA are summarised in figure 1 . Only 0.4% (33/763) of the total patient cohort received an Ex Rx. Ex Rx were provided to a number of patients with a personal history or family history of an inheritable cardiac condition ( figure 2 ). Conclusions: Compared to the general adult Irish population, self reported adherence to the WHO PA Guidelines was 6% lower among the CRY Clinic patient cohort (33% vs. 27%). Additionally, reported resistance exercise levels was lower (30%) than aerobic exercise (72%). This is despite resistance exercise being additionally beneficial for many cardiac conditions. During the period of data collection, access to gyms and group exercise was limited due to pandemic government restrictions that likely effected resistance exercise more than aerobic exercise. In fact, a significant increase in recreational walking during covid restrictions was previously reported. Exercise is often discussed during medical consultation but rarely prescribed. In our cohort only 0.5% of patients received an Ex Rx. The reported barriers to Ex Rx are lack of time, perceived lack of patient engagement, complex co-morbidities and clinician education. Attempts were made in the form of education and resource provision to clinicians to challenge perceived barriers. Ex Rx are important in the CRY Clinic not only for the known benefits of PA but as inappropriate exercise can be harmful for some cardiac conditions. The Ex Rx enabled the benefit of PA to be gained by the safe promotion of appropriate exercise to such patients ( figure 2 ). The introduction of this PA assessment and Ex Rx was a successful call to action to incorporate exercise as medicine to the CRY Clinic. 'Walking is a (wo)mans best medicine' (Hippocrates 460BC).